ANALISIS KEBUTUHAN MEDIA AUGMENTED REALITY BERBASIS LITERASI SAINS PADA MATERI EKOSISTEM DI SEKOLAH DASAR - Dellia Isti Agustin; Ghullam Hamdu; Muhamad Rijal Wahid Muharram (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study discusses the limitations of technology use in science learning in elementary schools, especially in ecosystem material. This study aims to analyze the need for AR-based media in improving students' science literacy. The method used is descriptive qualitative with data collection techniques through interviews, observations and documentation. Data analysis was carried out using the Miles and Huberman model which includes data collection, data presentation and drawing conclusions. The results of the study indicate that schools have adequate facilities but the integration of technology in learning is still limited due to constraints of readiness and internet quota, students experience obstacles in understanding the abstract concept of ecosystems. These findings indicate that AR-based media can support science literacy by providing interactive learning experiences that help students understand complex concepts more effectively. This study emphasizes the importance of integrating innovative learning media to improve science learning in elementary schools